Golden apple snail (Pomacea canaliculata) as an alternative protein source in Pasupati catfish (Pangasius sp.) fish feed - Meilisha Putri Pertiwi; Dina Dyah Saputri (Nusantara Bioscience, 2020)
Abstract. Pertiwi MP, Saputri DD. 2020. Golden apple snail (Pomacea canaliculata) as an alternative protein source in Pasupati catfish (Pangasius sp.) fish feed. Nusantara Bioscience 12: 162-167. Research on efforts to conserve golden apple snail (Pomacea canaliculata) meat has been done. This research aimed to utilize the snail meat as an alternative feed for the Pasupati catfish (Pangasius sp.). The research was carried out from May to August 2020. It began by collecting Pomacea canaliculata by hand sorting then processed into artificial feed/pellets. The research was CRD designed with 5 treatments and 3 replications. Pasupati catfish juvenil measuring 7.4 ± 0.8 cm and weighing 11.7 ± 0.5 g, was maintained for 21 days with a stocking density of 15 individuals/aquarium. Feeding as much as 8% of the biomass with a frequency of feeding 3 times a day at satiation. Variables measured were SGR, L, RP, FCR, and SR. The results showed that feed B produced the best fish growth and could be an alternative fish feed without having a negative effect on growth and feed utilization. Feed B (90% fish meal + 10% Pomacea canaliculata meat meal) had the highest SGR value and was supported by a high PR value and a low FCR value. In addition, there is a difference among variables, despite least significant. ANOVA test also supports the differences between treatments, but HSD test (p<0,05) is not significantly different. This means that the addition of the percentage of P. canaliculata meat meal to the feed does not provide a good performance of the Pasupati catfish. Value of abiotic parameters was ??to support fish farming.